Singing Mandarin? What Short-Term Memory Capacity, Basic Auditory Skills, and Musical and Singing Abilities Reveal About Learning Mandarin - Christiner, Markus; Renner, Julia; Groß, Christine; Seither-Preisler, Annemarie; Benner, Jan; Schneider, Peter (Frontiers in Psychology, 2022)
Learning Mandarin has become increasingly important in the Western world but is rather difficult to be learnt by speakers of non-tone languages. Since tone language learning requires very precise tonal ability, we set out to test whether musical skills, musical status, singing ability, singing behaviour during childhood, elementary auditory skills and short-term memory ability contribute to individual differences in Mandarin performance. Therefore, we developed Mandarin tone discrimination and pronunciation tasks to assess individual differences in adult participants’ (N=109) tone language ability. Results revealed that short-term memory capacity, singing ability, pitch perception preferences, and tone frequency (high versus low tones) were the most important predictors which explained individual differences in the Mandarin performances of our participants. Therefore, it can be concluded that training of elementary auditory skills, musical training including singing should be integrated in the educational setting for speakers of non-tone languages who learn tone languages such as Mandarin.